Cryptic genetic variation in brain gene expression precedes the evolution of cannibalism in spadefoot toad tadpoles - Dante J. Nesta; Cristina C. Ledón-Rettig (Proceedings of the National Academy of Sciences, 2025)
The origins of novel behaviors are poorly understood, despite behavior’s hypothesized roles in evolution. One model, “genetic accommodation,” proposes that selection on ancestral phenotypic plasticity may precede the evolution of novel traits. A critical assumption of genetic accommodation is that ancestral lineages possess heritable genetic variation for trait plasticity that is revealed in novel environments, thereby providing the raw materials for subsequent refinement of the novel trait in derived lineages. Here, we use a combination of behavioral and RNA-seq approaches to test this assumption in the context of a novel tadpole behavior: predatory cannibalism. Cannibalism evolved in the spadefoot genus Spea , where an invertebrate diet induces a carnivorous tadpole morph capable of consuming live conspecific tadpoles. In contrast, closely related Scaphiopus tadpoles do not induce this carnivorous phenotype. Through species comparisons, we found that ancestral Spea likely expressed behavioral plasticity and harbored latent (i.e., “cryptic”) genetic variation in brain gene expression plasticity associated with cannibalism-inducing cues. Further, we found that this cryptic genetic variation includes genes specifically associated with a dietary response and cannibalism in derived Spea . Our results suggest that novel behaviors, alongside novel morphologies, can evolve via the process of genetic accommodation. More generally, our results provide key evidence for the plausibility of genetic accommodation, revealing that cryptic genetic variation—the raw material for the evolution of novel traits—exists in natural populations at the level of gene expression.